Rapid Induction of Ageing Character in Brandy Products. Ageing and General Overview - van Jaarsveld, F.P.; Hattingh, S. (South African Journal of Enology and Viticulture, 2016)
Ageing is one of the most important and most costly factors determining the quality of distilled beverages. As part of a broader study that investigated techniques for the rapid induction of a desirable ageing character in brandy products, the effect of maturation for eight months at room temperature and below 0°C in glass bottles, and the relationship/correlation between treatment, chemical composition or wood-derived congener concentrations and pot-still brandy sensory quality, are reported on. Extracts representing different oak types (American or French), levels of toasting, suppliers (i.e. cooper or commercial), types of medium (ethanol or water), concentration types (open or reduced pressure) and concentration levels (by 45, 65 or 85%) were added to pot-still spirit and stored for eight months in glass containers. Matured and unmatured (control) pot-still brandy samples were analysed for wood-derived compounds by means of HPLC and GC. The different treatments brought about chemical changes with a noticeable impact on the acceptability of oak extracts and the overall quality of pot-still brandies. Through application and selection of the correct oak type and treatment combinations, it therefore was possible to rapidly produce good quality brandies without the use of expensive oak barrels. Maturation in glass bottles had a lesser impact on further improvement of the final product, not the same as the reported improvement from ageing in wooden barrels. The production of good quality brandies and the rapid induction of the ageing character through certain treatment combinations, with little need for further maturation, therefore was achieved in glass. The complexity of brandies aged in glass rather than wooden barrels might be different, since ageing in wooden barrels brings about all the characteristics, complexities and flavours that characteristically evolve over time under the more oxidative conditions in wooden barrels. Future research should focus on a combination of both technologies, using certain oak treatment combinations together with traditional barrel maturation for the improvement and rapid induction of the ageing character in brandy products.